2007
DOI: 10.1134/s1087659607040037
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the formation of nanorolls

Abstract: Models of the formation of nanorolls in fluid media are constructed. The successive stages of the detachment of a stressed double nanolayer with the subsequent twisting into a nanoroll are calculated by the molecular dynamics method. The dynamics of twisting with the formation of a multiwalled nanoroll is described within a continuous model. The results of simulating the formation of different configurations of nanorolls during their diffusion growth are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Critical nuclei appear to be formation is the intercalation of water between structural layers during deformation followed by strain release through a mechanism featuring layer separation followed by coiling (Chivilikhin et al 2007). Though not a property of separated nanoparticles, this kind of process relates stress reduction and hydration reactions to each other on the nanoscale, whereas entirely different strain release mechanisms ostensibly occur at larger scales.…”
Section: Silica Silicates and More Common Mineralsmentioning
confidence: 99%
“…Critical nuclei appear to be formation is the intercalation of water between structural layers during deformation followed by strain release through a mechanism featuring layer separation followed by coiling (Chivilikhin et al 2007). Though not a property of separated nanoparticles, this kind of process relates stress reduction and hydration reactions to each other on the nanoscale, whereas entirely different strain release mechanisms ostensibly occur at larger scales.…”
Section: Silica Silicates and More Common Mineralsmentioning
confidence: 99%
“…However, it should be noted that the mechanism of formation of nanorolls involves not only the important stage of twisting of nanolayers but also a sequence of different processes, which occur both sequentially and concurrently and result eventually in the formation of nanocrystalline or heterostructural nanotubes. In particular, the mechanism of formation of nanotubes with a chrysotile structure was studied in [21][22][23][24][25]. It was shown that, in a number of cases, the formation of nanorolls can be limited by crystallization of the initial compound with a layered structure.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the layers of this compound can form nanorolls either upon their direct twisting or upon twisting of subsequent layers formed after a sequence of chemical transformations of the initially formed chemical compound with a layered structure. In this case, the chemical composition and the structure of initial components appear to be important factors that affect the formation of crystalline nanorolls [12,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…For example, some works describe the spontaneous rolling up of nanolayers under the action of internal forces [3,4]. In the present work, an attempt is made to describe the rolling up of nanotubes in a liquid medium from the standpoint of the energy balance in a system consisting of a nanometer-size thin film and molecules which sorb from solution onto the film's surface.…”
mentioning
confidence: 99%